PENGARUH KEMAMPUAN DASAR DAN PENDUKUNG TERHADAP KOMPETENSI SISWA AKUNTANSI SEKOLAH MENENGAH KEJURUAN - Contessa, Emilia; Aziza, Nurna (JURNAL FAIRNESS, 2016)
The purpose of this research is to examine the influence of basic of capability SMK’S student Mathematic, Bahasa Indonesia, English, Fundamental Accounting, Financial Accounting and Cost Accounting. The sample of this study concaist of 111 student of SMKS 11 2014th. The study found that the capability SMK’S student in Mathematic, Fundamental Accounting, Financial Accounting give positively influence to student competency skill. Meanwhile the variable of basic Indonesia language, English language, and Cost Accounting did not give positive influence to student competency. The implemention can be used as input in the process of learning to prepare SMK graduate wits good quality and to increase the knowledge and development of future research. Therefore, capability of Mathematic, Fundamental Accounting, and Financial Accounting should be improved more than before.